Requirements traceability in automated test generation application to smart card software validation. - Bouquet, F.
Automated test case and test driver generation from a formal model is becoming a more widely used practice in the smart card area. This innovative approach for validation testing makes it possible to ensure the functional coverage of the test suite and to automate the production of executable test scripts. This paper presents an approach to automatically produce the Traceability Matrix from requirements to test cases, as part of the test generation process. This approach is embedded in the LEIRIOS Test Generator (LTG) tool, and has been used for several real-life applications in the smart card industry. This paper introduces the approach to annotating the formal model and using it to generate the Traceability Matrix. It also discusses some lessons learnt from our experience using Model-Based Testing for smart card software validation.
Keywords: Software; Software engineering; Requirements/Specifications.; Testing and debugging; Reliability; Verification; Formal model; Model-based testing; Requirements traceability